STRATEGI PENETRASI PASAR UNTUK MENINGKATKAN DAYA SAING PERUSAHAAN E-COMMERCE DI INDONESIA - Zhulaydar Esa Putri; Nida Khoirun Nahda Labibah; Zulfa Fauziah Irsyada Baidlowi; Diah Novita Sari; Kirena Farah Asmaranti; Ilham Akbar Abiyasa (JMB : Jurnal Manajemen dan Bisnis, 2021)
This research aims to describe the market penetration strategies used by companies, especially the Indonesian e-commerce industry, to increase their competitiveness. This research occupies a qualitative method toward Indonesia’s e-commerce industry, especially the three dominating companies, such as Shopee, Tokopedia, and Bukalapak. This study uses descriptive research, and our data sources are documents and literature about market penetration strategies conducted by e-commerce industries. The result showed that their strategy to do the market penetration is price adjustment, cooperation, or collaboration, offering some special promos, developing the features and services, and using artists and influencers as brand ambassadors.Keywords: Economy, Strategic Management, Market Penetration, Competitiveness, E-Commerce